Proportions and trends of global adolescent knowledge and attitudes toward tobacco smoking from 1999 to 2019 - Xie, Jintang; Ma, Chuanwei; Yang, Hui; Gong, Zhuo; Zhao, Min; Magnussen, Costan G.; Xi, Bo (Frontiers in Public Health, 2025)
ObjectiveWe aimed to assess the recent levels of knowledge and attitudes toward tobacco smoking among adolescents aged 12–16 years in 2010–2019, and to examine trends from 1999 to 2019.MethodsWe used the most recent data from 145 countries/territories (hereafter “countries”) that conducted at least one Global Youth Tobacco Survey (GYTS) between 2010 and 2019 to assess the current levels of knowledge and attitudes toward tobacco smoking among adolescents aged 12–16 years. And 112 countries that conducted at least three GYTS surveys from 1999 to 2019 were used to assess the trends among adolescents aged 12–16 years over time.ResultsAmong 570,492 adolescents from 145 countries, 13.9% (95% CI, 11.9%−15.8%) incorrectly believed that tobacco smoking was not harmful, and 16.1% (95% CI, 15.2%−16.9%) believed that exposure to secondhand smoke was not harmful. A substantial proportion believed that quitting smoking was easy (42.5%; 95% CI, 36.9%−48.0%) or that short-term smoking was safe if followed by quitting (40.2%; 95% CI, 39.1%−41.3%). Additionally, 25.8% (95% CI, 24.8%−26.8%) believed that tobacco smoking helps young people feel more comfortable, 26.4% (95% CI, 24.8%−28.0%) believed that it helps them make more friends, and 15.8% (95% CI, 14.6%−17.0%) believed that it makes them appear more attractive. Among 1,734,258 adolescents from 112 countries, 67.9% of countries showed increasing or stable trends in the belief that smoking is not harmful, 75.9% for the belief that secondhand smoke exposure is not harmful, 38.4% for short-term smoking being safe, 32.1% for quitting being easy, and 69.6, 43.8, and 44.6% for the beliefs that smoking helps with comfort, making friends, and appearing attractive, respectively, from 1999 to 2019.ConclusionsIncorrect beliefs and positive attitudes toward tobacco smoking were prevalent among adolescents worldwide. Moreover, these beliefs and attitudes toward tobacco smoking have either persisted or increased in most included countries over time. Targeted interventions and policies are needed to reduce these and promote accurate knowledge about tobacco use and its harmful effects.